Mixed-Integer Programming to Solve Distribution Problems - Kamil Oruçoğlu; Elif Adaköy; Melis Mumcuoğlu; Seray Şengül; Gökhan Göksu (Journal of New Results in Science)
Mixed-integer linear and quadratic programming problems are considered to solve distribution problems in this paper. The first problem is the distribution of proctors with respect to the student placements to the class- rooms by mixed-integer linear programming whereas the second problem is the fair distribution of the workloads for teaching assistants in a department formulated by mixed-integer quadratic programming. Three approaches to find the solution for mixed-integer quadratic programming problem are proposed and a comparative example is given to measure the effects for the suggested criterion.